From joint to heart: Cardiovascular implications of rheumatoid arthritis - Raharjo, Fajar; Anjarwani, Setyasih (PT. DEKA RESEARCH INSTITUTE, 2024)
Rheumatoid arthritis is a commonly encountered autoimmune disease and a progressive chronic inflammatory condition that often leads to permanent joint damage. Systemic inflammation in rheumatoid arthritis is linked to various comorbid conditions such as interstitial lung disease, osteoporosis, metabolic syndrome, cardiovascular disease, infections, malignancies, cognitive dysfunction, depression, and fatigue, which can increase morbidity and mortality in rheumatoid arthritis patients. Approximately 36% of patients report worse health and limitations in daily activities, while nearly 30% require more assistance with personal care compared to individuals without rheumatoid arthritis. Epidemiological data from 1990 to 2017 show an incidence of rheumatoid arthritis of 246.6 per 100,000 people aged 33-54 years, with prevalence in women 2-3 times higher. In Southeast Asia, the incidence is 89 per 100,000 in individuals aged 13-22 years, while in Indonesia, it is estimated at around 5-7.5 per 100,000 population. Cardiovascular disease is the primary cause of mortality in rheumatoid arthritis patients, with myocardial infarction being the major contributor. The pathogenesis of rheumatoid arthritis is still complex and involves immunological processes that occur long before joint inflammation symptoms appear, including genetic modifications and environmental factors that lead to deimination and joint disturbances. Cardiovascular manifestations, particularly myocardial infarction, occur due to an atherosclerotic process triggered by rheumatoid antibody complexes. Given the higher cardiovascular risk in rheumatoid arthritis patients, early detection and awareness of these manifestations are crucial for better management.